2005
DOI: 10.1002/elan.200503303
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Selenium with a Poly(1,8‐diamino‐naphthalene)‐Modified Electrode

Abstract: The performance of a poly(1,8-diaminonaphthalene)-modified electrode for the determination of the Se(IV) ion in an aqueous medium was investigated with anodic stripping voltammetry without the pretreating of the sample. The experimental parameters for the analysis of Se(IV) were optimized and the characteristics of this polymer-modified electrode were investigated by using cyclic voltammetry. The Se(IV) ions were chemically deposited onto the surface of the pDAN-Au electrode in an acidic medium. The detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In comparison with typical CPs such as PPy, PANi and PTh, CPs from aromatic diamines have lower electrical conductivity, but they have a unique ability to form stable complexes with HM ions. Many references reported that polydiaminonaphthalene (PDAN) could chelate Cu 2+ [ 77 , 78 ], Hg 2+ , Ag + [ 79 , 80 ], Se(IV) [ 81 ] or Pb 2+ , probably via free -NH 2 groups. For example, Majid et al [ 82 ] used a poly(1,8-diaminonaphthalene)-modified electrode to detect Pb 2+ by ASV, with a preconcentration step at a potential of −0.9 V vs .…”
Section: Conducting Polymer-modified Electrodesmentioning
confidence: 99%
“…In comparison with typical CPs such as PPy, PANi and PTh, CPs from aromatic diamines have lower electrical conductivity, but they have a unique ability to form stable complexes with HM ions. Many references reported that polydiaminonaphthalene (PDAN) could chelate Cu 2+ [ 77 , 78 ], Hg 2+ , Ag + [ 79 , 80 ], Se(IV) [ 81 ] or Pb 2+ , probably via free -NH 2 groups. For example, Majid et al [ 82 ] used a poly(1,8-diaminonaphthalene)-modified electrode to detect Pb 2+ by ASV, with a preconcentration step at a potential of −0.9 V vs .…”
Section: Conducting Polymer-modified Electrodesmentioning
confidence: 99%
“…This sensor exhibited a long lifetime and high sensitivity for the H + ion. Poly (1,8-diaminonaphthalene)-modified electrode has been developed for the determination of the Se(IV) ion in an aqueous medium and investigated with anodic stripping voltammetry without pre-treating the sample and by using cyclic voltammetry [ 38 ]. The detection limit employing the anodic stripping differential pulse voltammetry was 9.0 × 10 −9 M for Se (IV).…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…The performance of a poly(1,8-diaminonaphthalene)-modified gold electrode for the determination of the Se(IV) ion in an aqueous medium was investigated with anodic stripping voltammetry. The detection limit employing the anodic stripping differential pulse voltammetry was 9.0 x10 -9 M for Se(IV) with 4.4 % of RSD% [5]. DPCSV determination of Se (IV) from pharmaceutical products was applied.…”
Section: Introductionmentioning
confidence: 99%